A Comparative Overview of Epigenomic Profiling Methods - Mehrmohamadi, Mahya; Sepehri, Mohammad Hossein; Nazer, Naghme; Norouzi, Mohammad Reza (Frontiers in Cell and Developmental Biology, 2021)
In the past decade, assays that profile different aspect of the epigenome have grown exponentially in number and variation. However, standard guidelines for researchers to choose between available tools depending on their needs are lacking. Here, we introduce a comprehensive collection of the most commonly used bulk and single-cell epigenomic assays and compare and contrast their strengths and weaknesses. We summarize some of the most important technical and experimental parameters that should be considered for making an appropriate decision when designing epigenomic experiments